A genetically encoded probe for imaging nascent and mature HA-tagged proteins in vivo - Ning Zhao (Nature Portfolio, 2019)
Expression of genetically encoded antibodies for cell labelling is often limited by folding issues. Here, the authors engineer an anti-HA scFv antibody that works in the cellular environment and use it to track mRNA translation dynamics in living cells and to label proteins in live zebrafish embryos.